2011
DOI: 10.1097/ana.0b013e3181f35854
|View full text |Cite
|
Sign up to set email alerts
|

Serial Measurement of Static and Dynamic Cerebrovascular Autoregulation After Brain Injury

Abstract: Daily measured dAR and sAR were impaired after brain injury with a nadir on day 4 and consecutive incomplete recovery over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 22 publications
1
24
1
Order By: Relevance
“…Explanations of this temporal evolution are, however, difficult; in contrast to the scant studies on the time course of ICP after injury, this is the only study (to our knowledge) to assess continuous cerebral vascular reactivity in relation to time from injury. In contrast to our findings, investigations intermittently assessing pressure autoregulation using transcranial Doppler have found impaired pressure autoregulation in the first 4–5 days postinjury before a gradual return towards normal values [4245]. Cerebrovascular reactivity can be seen as a proxy variable of various neuropathophysiological processes and interventions that can modulate it.…”
Section: Discussioncontrasting
confidence: 99%
“…Explanations of this temporal evolution are, however, difficult; in contrast to the scant studies on the time course of ICP after injury, this is the only study (to our knowledge) to assess continuous cerebral vascular reactivity in relation to time from injury. In contrast to our findings, investigations intermittently assessing pressure autoregulation using transcranial Doppler have found impaired pressure autoregulation in the first 4–5 days postinjury before a gradual return towards normal values [4245]. Cerebrovascular reactivity can be seen as a proxy variable of various neuropathophysiological processes and interventions that can modulate it.…”
Section: Discussioncontrasting
confidence: 99%
“…The index of AR Mx was measured on a daily basis during the first 4 days after the onset of sepsis, showing an increased index Mx and, thereby, a disturbed AR during the first 2 days of sepsis followed by a recovery of AR during the next two days. This time course with initial impaired AR followed by a recovery was also observed in patients with intracranial lesions [19]. The question of whether the disturbance of AR is a clinical sign of critically ill patients in general, or a typical problem of septic patients, cannot be answered by the present study.…”
Section: Discussionmentioning
confidence: 51%
“…Within 7 days of serial measurements, Schramm et al demonstrated that both dynamic and static CA were impaired after severe brain injury and that ICH patients with a nadir on day 4 subsequently experienced an incomplete recovery over time. 21 Yet, with a study length of 1 month, we found a prolonged impairment of dCA for at least 10 to 12 days post ictus. Moreover, PD and RoRc values indicated the worst autoregulation at that time point.…”
Section: March 2016mentioning
confidence: 95%